HUBUNGAN ANTARA FLEKSIBILITAS SENDI BAHU DAN POWER OTOT LENGAN DENGAN KECEPATAN SMASH DALAM OLAHRAGA BULUTANGKIS - Mi'rajul Taufik; Andi Gilang Permadi; Kurnia Taufik (Universitas Pendidikan Mandalika, 2017)
Background of badminton playing ability at 10-year-old athlete O2SN athletes is very important, especially in achieving badminton achievement. The problem that arose in this research is the relationship between flexibility of shoulder joint and arm muscle power with smash speed in badminton sport. Badminton is one of the most popular sports, attracting different age groups, different skill levels for both men and women. Badminton games will be more interesting where the teacher / trainer creative in the development of the forms of teaching. The formulation of the problem in this research with the title